Sensory profiling of pears from the Pacific Northwest: Consumers' perspective and descriptive analysis - Montero Díaz, María Laura (2024)
This study used data from consumer testing, descriptive analysis (DA), and preference mapping to determine the sensory characteristics of pear cultivars from two harvest seasons in the Pacific Northwest (PNW). A trained sensory panel (n = 10) used generic DA to evaluate multiple sensory modalities of 22 pear cultivars. Six pears from summer and six from winter season were evaluated by consumers (n = 219) to assess their liking of different attributes. Results of the DA showed the trained panel significantly discriminated the summer and winter pears on most of the sensory modalities. To identify the attributes driving consumer acceptability, external preference mapping was applied. Attributes such as pear aroma, pear flavor, sweet, sour, and juicy were the most contributory attributes to the liking of the summer pears. Conversely, fermented aroma, stemmy–woody aroma, fermented flavor, stemmy–woody flavor, and grainy–gritty attributes were associated with a reduction in consumer liking. Summer cultivars, “Bartlett,” coded pear 573, and “Seckel” had the broadest preference, satisfying 60% to 80% of the consumers. Seventy-five percent of the consumers identified winter cultivars “Comice” and “Paragon” as the most appealing. Overall, cluster analysis showed that different pears appeal to different types of consumers; however, summer cultivars like “Bartlett” and “Seckel” and winter cultivars like “Comice” and “Paragon” would appeal to the greatest number of consumers in the PNW market.